1976
DOI: 10.1073/pnas.73.11.3999
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance studies of the interaction of general anesthetics with 1,2-dihexadecyl-sn-glycero-3-phosphorylcholine bilayer.

Abstract: Under ultrasonic irradiation, 1,2-dihexadecyl-sn-glycero-3-phosphorylcholine (DHDPC) forms microvesicular liposomes in D20. These liposomes have been widely used as a model of a cell membrane.We have studied the interaction of some general anesthetics, i.e., chloroform, halothane, methoxyflurane, and enflurane, with synthetic DHDPC-D2O liposomes by Fourier transform proton magnetic resonance (PMR). Our previous work (1) showed that chloroform and halothane interacted with DHDPC-D20 liposomes (about 1.5-2% wt/w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…They concluded that the interaction between halothane and the lipid bilayer occurs in the headgroup region. This idea of the water interface being the primary localization of the anesthetic was also supported by Shieh et al, (1976) in a proton NMR study of 1,2-dihexadecyl-sn-glycero-3-phosphorylcholine (DHDPC) liposomes and Tsai et al (1987) in an IR study of halothane in reverse DMPC/water/benzene micelles. The same IR technique was also used for halothane in DPPC vesicle membranes (Tsai et al, 1990).…”
Section: Introductionmentioning
confidence: 81%
“…They concluded that the interaction between halothane and the lipid bilayer occurs in the headgroup region. This idea of the water interface being the primary localization of the anesthetic was also supported by Shieh et al, (1976) in a proton NMR study of 1,2-dihexadecyl-sn-glycero-3-phosphorylcholine (DHDPC) liposomes and Tsai et al (1987) in an IR study of halothane in reverse DMPC/water/benzene micelles. The same IR technique was also used for halothane in DPPC vesicle membranes (Tsai et al, 1990).…”
Section: Introductionmentioning
confidence: 81%
“…In general, anesthetics increase the fluidity of the membrane phase; that is, they induce a transition from gel to crystalline liquid in the same manner as an increase in temperature (102,133). The anesthetic-induced shift in transition temperature (134) suggests that the pool size of melted lipids has increased.…”
Section: Fluidizationmentioning
confidence: 96%
“…These membranes undergo a main chain melting transition between a liquid phase and gel or solid phases, whose properties have been extensively studied by a variety of experimental methods. In all cases, incorporating hydrophobic general anesthetics into single component membranes lowers the main chain transition temperature (T M ) and disorders lipid chains (makes their motions more isotropic) at fixed temperature (Shieh, Ueda, Lin and Eyring 1976; Kamaya, Ueda, Moore and Eyring 1979; Miller, Firestone, Alifimoff and Streicher 1989; Heimburg and Jackson 2007; Lorincz, Mihaly, Nemeth, Wacha and Bota 2015). These molecules also can impact the lateral pressure profiles, bending rigidity, and water permeability of simple membranes (Trudell, Payan, Chin and Cohen 1975; Mountcastle, Biltonen and Halsey 1978; Gruner and Shyamsunder 1991; Jorgensen, Ipsen, Mouritsen, Bennett and Zuckermann 1991; Jorgensen, Ipsen, Mouritsen and Zuckermann 1993).…”
Section: Introductionmentioning
confidence: 99%